Proceedings of the 2020 CHI Conference on Human Factors in Computing Systems 2020
DOI: 10.1145/3313831.3376186
|View full text |Cite
|
Sign up to set email alerts
|

Move Your Body: Engaging Museum Visitors with Human-Data Interaction

Abstract: Figure 1. Museum visitors interact with our prototype Human-Data Interaction system using gestures and body movements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 54 publications
1
25
0
Order By: Relevance
“…Chatain et al brought the users' bodies to the core of the digital experience by using their hands as a controller and a display, both for games and playful educational activities [9]. Trajkova et al used embodied interaction for data exploration in a museum context and found that the representation of the bodies impacted the gestures used to interact with digital content [56]. Focusing specifically on learning, Lindgren and al.…”
Section: Embodied Interactionmentioning
confidence: 99%
“…Chatain et al brought the users' bodies to the core of the digital experience by using their hands as a controller and a display, both for games and playful educational activities [9]. Trajkova et al used embodied interaction for data exploration in a museum context and found that the representation of the bodies impacted the gestures used to interact with digital content [56]. Focusing specifically on learning, Lindgren and al.…”
Section: Embodied Interactionmentioning
confidence: 99%
“…Novel approaches such as somaesthetic appreciation design [94,95] describe the manner in which users' bodies may be integrated in the design process as well as in the experience with digital content and data. Empirical evidence suggests that bodies' representations impact the sense of embodiment [96,97], as well as the types of gestures performed to interact with a system and the time spent observing and interacting with data [98]. In this regard, the challenge of FTs extends beyond meaningfully anchoring virtual data onto a physical context to include the design of the interaction with the augmentation from an embodied, somaesthetic perspective [74,94,95].…”
Section: Situated Analyticsmentioning
confidence: 99%
“…Before video streaming platforms were omnipresent, television channels, and especially public service media channels, directed the programming of their Saturday evening to families, with the goal of establishing social interaction between them through game shows and comedy. Similarly, museums are also involved in designing narratives for family experiences [41], which might be exploited in data exploration contexts as well [35].…”
Section: Related Workmentioning
confidence: 99%